Extracranial metastatic oligodendroglioma with molecular progression, case presentation - Nour Kurdi; Attila Mokánszki; Ingrid Balogh; Anikó Ujfalusi; Sándor Szabó; Gábor Méhes; Judit Bedekovics (BMC, 2024)
Abstract Background Extraneural metastasis of central nervous system tumors is generally rare and most often reported in glioblastomas and medulloblastomas, whereas oligodendrogliomas seem to have the lowest risk of extracranial metastasis. Given its infrequent occurrence, both the diagnosis and therapy of metastatic oligodendroglioma is often challenging. Case presentation This case study presents an oligodendroglioma, the isocitrate dehydrogenase 1 (IDH1) mutant, 1p/19q-codeleted tumor with bone marrow metastasis. The significance of this case lies in the comprehensive molecular analysis conducted for both the primary tumor and the metastasis. Chromosome 7 trisomy and chromosome 10 monosomy (+ 7/-10) were detected in the metastasis indicating molecular progression, which, to the best of our knowledge, has not been previously documented in metastatic oligodendroglioma. Conclusions This case study serves additional information for better understanding of the metastatic capabilities of CNS tumors.